Differences in Fatigue Levels Based on Work Shifts in Concrete Production Workers - Maulana, Ikhsan; Utami, Tri Niswati; Nanda, Meutia (Indonesian Journal of Global Health Research, 2024)
The increase in demand for concrete raises demands for high production needs so that complaints of fatigue arise in workers. In an effort to minimize fatigue felt by workers, the company implements a shift system at work. The purpose of this study was to determine the difference in fatigue levels based on work shifts in concrete production workers of PT. Maxima Daya Indonesia. This study used quantitative methods with a cross sectional design. The population in this study was all workers with a sampling technique, namely a total sampling technique of 104 respondents. The ariables studied in this study were shift work and work fatigue. The data will be tested for normality and homogeneity and then analyzed using a t-independent test to determine the difference between the two variables that are statistically meaningful. The results of this study showed a significant difference between the average fatigue in the morning shift with the night shift (sig<0.005) with the mean in the morning shift of 32.33 while the mean in the night shift was 38.56. Fatigue in the night shift caused by night shift work activities tends to be the same as the morning shift and disrupted workers' rest patterns.